Study The Various Types of Allergies, and Its Correlation with Blood Grouping Among Medical Technology Students in Derna - Arig Alyasir; Zaynab Alzalawi; Rawan Busheha; Maryam Dardak; Hadeel Juwayli; Abdualkarim Alzouki (المجلة الأفروآسيوية للبحث العلمي, 2025)
When the immune system overreacts to chemicals that do not affect the majority of people, a condition called allergies or hypersensitivity reactions develops. Pollen, animal dander, chemicals, fungi, or foods like nuts, eggs, shellfish, fish, and milk are examples of these substances, which are also known as allergens. A variety of illnesses, mostly affecting the skin but also affecting other organs like the liver, kidneys, and lungs, can be caused by immune reactions to small molecule compounds like drugs. Due to the significance of genetic factors, this study aimed to analyze the relationship between blood grouping and various types of allergies among medical technology students in Derna in 2023. It was survey-based research that used questionnaires (51 questionnaires) that were distributed to college students before data was collected and analyzed. The questionnaire included questions about the kind of allergy, blood group, symptoms, treatment, and if any family members had the same allergy. The blood group with the greatest proportion of all types of allergies included in this study was blood group A+, followed by blood group O+, which was the second highest blood group among all types of allergies. As a result, there was a connection between blood groups and different kinds of allergies.